Platinum nanoparticles embedded into polyaniline on carbon cloth: improvement of oxygen reduction at cathode of microbial fuel cell used for conversion of medicinal plant wastes into bio-energy. Issue 9 (16th April 2022) - Zerrouki, Aicha; Kameche, Mostefa; Ait Amer, Ahcene; Tayeb, Ahlem; Moussaoui, Douniazeed; Innocent, Christophe
ABSTRACT: A microbial fuel cell is a biological electrochemical system that extracts electrons stored in organic matter by oxidation using catalytic properties of microorganisms at bioanode. The major problem in such device, is however limited power production due to slow kinetic of oxygen reduction at cathode. It is worthwhile to develop new materials that fulfil these requirements. The polymerization of aniline onto carbon cloth for effective electrodeposition of platinum nanoparticles has been carried out by chronoamperometry and cyclic voltammetry. Three materials were thus elaborated, namely pristine carbon cloth, carbon cloth modified with platinum and carbon cloth modified by polymerization of aniline for immobilization of Pt-nanoparticles. The FTIR spectroscopy analysis revealed characteristic band located in 1720–1650 cm −1, attributed to imine function, main component in skeleton of polymer PANI chain. The modified materials have been utilized as cathode in cell inoculated with medicinal plant wastes for improvement of oxygen reduction. Modified cathode with CC-PANI-Pt proved higher performances in all respects: increase of cell voltage from 338 to 765 mV and power density from 862 to 1510 mW/m 2 and abatement of COD of microbial inoculum leachate to 88%. Another feature of cell with modified cathode CC-PANI-Pt, was the enormous electric charge density harvested upon oxidation of 1 mL of acetate 7.62 C/cm 2 compared to that of cell with pristine CC cathode 0.54 C/cm 2 . Nevertheless, coulombic efficiency for conversion of medicinal plant wastes into bioenergy was relatively lower 9%, making in evidence that elaborated electrochemical device was rather efficient and benificial environmentally than energetically. GRAPHICAL ABSTRACT: UF0001